Susceptibilidade de Spodoptera frugiperda (J.E Smith, 1797) (Lepidoptera: Noctuidae) a diferentes produtos à base de Bacillus - Lara, Charles Almeida (2023)
The fall armyworm, Spodoptera frugiperda, is a key pest of corn crops, highly mobile and polyphagous, being one of the most destructive species with great economic importance for several crops, representing a large part of the production cost. Aiming at strategies for managing this pest, the use of chemical, biological products and/or genetically modified plants with genes (Bt), normally derived from the entomopathogenic microorganism Bacillus thurigiensis, are commonly used. However, the strategies currently adopted for control already present cases of resistant populations of S. frugiperda throughout the national territory. Biological control using pathogenic bacteria such as Bacillus thurigiensis has been used as the main control alternative, both in genetically modified plants and in formulated products, which has increased the selection pressure for resistant populations. Therefore, the use of microorganisms other than the thurigiensis species may be an alternative aimed at reducing resistance. Therefore, the objective of this work was to evaluate the synergism between different Bacillus such as Bacillus subitilis, Bacillus licheniformis, Bacillus amyloliquefaciens, some with a mixture of Bacillus thurigiensis, in the control of Spodoptera frugiperda through an ingestion bioassay under laboratory conditions to verify the possibility of fall armyworm control.